Novel Use of Vitamin B2 as a Fluorescent Tracer in Aerosol and Droplet Contamination Models in Otolaryngology. (March 2021) - Sim, Edward S.; Dharmarajan, Harish; Boorgu, Devi Sai Sri Kavya; Goyal, Lindsey; Weinstock, Michael; Whelan, Rachel; Freiser, Monika E.; Corcoran, Timothy E.; Jabbour, Noel; Wang, Eric; Chi, David H.
Objective: During the COVID-19 era, a reliable method for tracing aerosols and droplets generated during otolaryngology procedures is needed to accurately assess contamination risk and to develop mitigation measures. Prior studies have not investigated the reliability of different fluorescent tracers for the purpose of studying aerosols and small droplets. Objectives include (1) comparing vitamin B2, fluorescein, and a commercial fluorescent green dye in terms of particle dispersion pattern, suspension into aerosols and small droplets, and fluorescence in aerosolized form and (2) determining the utility of vitamin B2 as a fluorescent tracer coating the aerodigestive tract mucosa in otolaryngology contamination models. Methods: Vitamin B2, fluorescein, and a commercial fluorescent dye were aerosolized using a nebulizer and passed through the nasal cavity from the trachea in a retrograde-intubated cadaveric head. In another scenario, vitamin B2 was irrigated to coat the nasal cavity and nasopharyngeal mucosa of a cadaveric head for assessment of aerosol and droplet generation from endonasal drilling. A cascade impactor was used to collect aerosols and small droplets ≤14.1 µm based on average aerodynamic diameter, and the collection chambers were visualized under UV light. Results: When vitamin B2 was nebulized, aerosols ≤5.4 µm were generated and the collected particles were fluorescent. When fluorescein and the commercial water tracer dye were nebulized, aerosols ≤8.61 µm and ≤2.08 µm respectively were generated, but the collected aerosols did not appear visibly fluorescent. Endonasal drilling in the nasopharynx coated with vitamin B2 irrigation yielded aerosols ≤3.30 µm that were fluorescent under UV light. Conclusion: Vitamin B2's reliability as a fluorescent tracer when suspended in aerosols and small droplets ≤14.1 µm and known mucosal safety profile make it an ideal compound compared to fluorescein and commercial water-based fluorescent dyes for use as a safe fluorescent tracer in healthcare contamination models especially with human subjects.